Developing and Testing Digital Ethical Reflection in Long-Term Care: Nurses' Experiences - Lena Jakobsen PhD; Rose Mari Olsen RN, PhD; Berit Støre Brinchmann RN, PhD; Siri Andreassen Devik RN, PhD (SAGE Publishing, 2023)
Introduction Nurses working in municipal long-term care face ethical challenges that can lead to moral distress and discomfort for the nurse and affect the quality of patient care. Tools and methods that contribute to increased ethical awareness and support for nurses dealing with moral issues are lacking. Technological innovations may be suitable for ethics work, but little research has been conducted on how such solutions could be designed or their potential benefit. Therefore, this study contributes knowledge about the development and testing of a digital tool for ethics support among nurses. Objective To investigate how digital ethical reflection can support ethics work among nurses working in long-term care. Methods A digital ethical reflection tool was designed and tested in nursing homes and home nursing care in collaboration with two Norwegian municipalities. The study used sequential explanatory mixed-methods design. Over a 6-week period, at the end of each shift, nurses digitally reported the ethical challenges they had experienced. Their responses and experiences were described using descriptive statistics. Additionally, focus group interviews were conducted and analyzed using reflexive thematic analysis (TA). Results During the study period, 17 nurses reported a total of 223 registrations, with 24.8% stating that they had been in an ethically difficult situation. The digital reporting was perceived as practically applicable and helped to increase nurses' awareness of morally charged situations. The value of the registrations was found to depend on manager participation and the application of the obtained information. The participating nurses become aware that they lacked an arena for meaningful dialogue with and recognition from their manager. Conclusions Information obtained through digital reflection can form the basis for ethical reflections at the departmental level. Digital reflection has the potential to become a tool for managers in their support for employees facing ethical challenges when providing long-term care.